(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
The aim of the research is to identify the type of relationship between the variables of psychological loneliness, anxiety and depression, and to identify the extent of the contribution of psychological loneliness and anxiety to depression. Research community: The research community consists of students of both sexes who study at the undergraduate level during the academic year (2020-2021). Research tool: Use the closed and open questionnaire as a means of collecting data for this research. The results of the induction: - It was found that the feeling of most of the respondents with anxiety, depression and psychological loneliness is almost the same, whether for those who use Twitter or YouTube or not. - It was found that anxiety contributes more to depression when it interacts with the contribution of psychological loneliness, which confirms that anxiety is indeed the core and nucleus of neurosis.